National energy governance in the implementation of energy intensity, carbon emissions, and general energy fuel - Suryaningsum, Sri (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to provide an understanding of national energy governance in the implementation of energy intensity, carbon emissions, and general energy fuel (coal and oil and gas minerals) in Indonesia. This study analyzes national energy governance in the implementation of energy intensity, carbon emissions, and general energy fuel (coal and oil and gas minerals). The study was conducted using a qualitative descriptive research approach, focusing on transportation modes, in this case, as they generate carbon emissions during movement.The study results indicate that the implementation of carbon emissions generated by transportation modes has a reciprocal impact on national energy governance in the implementation of energy intensity, carbon emissions, and general energy fuel (coal and oil and gas minerals) in Indonesia.Estimated CO2 emissions from transportation modes. Estimated CO2 emissions for a trip from Yogyakarta to Jakarta: by train, 7.43 kg CO2 is produced, by car, 27.12 kg CO2 is produced, and by airplane, 65.17 kg CO2 is produced. These carbon emissions results indicate that the lowest is the train mode. Transportation carbon emissions originate from general energy fuel sources (coal and oil and gas), specifically from the combustion of fuels (gasoline, diesel, aviation fuel). The relative energy intensity of cars compared to trains is about ≈ 3.6 times and the relative energy intensity of airplanes compared to trains is about ≈7.9 times. The relative carbon emission of cars compared to trains is about ≈ 3.6 × and the relative carbon emission of airplanes compared to trains is about ≈ 8.7 ×These fuel sources are still entirely dependent on the oil and gas sector. Every increase in mobility means an increase in demand for petroleum. This demonstrates the need for energy governance policies that integrate the transportation and upstream mining sectors. The implementation of transportation modes in producing carbon emissions is inseparable from the use of energy intensity. The dynamics of energy intensity are directly proportional to the type of fuel and the efficiency of the engine system.